Sub‐population analysis of patients with plaque psoriasis treated with calcipotriol/betamethasone aerosol foam; effectiveness and patient satisfaction, according to baseline disease severity and prior psoriasis treatment experience, in a Greek population. Issue 6 (9th May 2022) - Rigopoulos, Dimitrios; Lazaridou, Elisavet; Papadavid, Evangelia; Georgiou, Sophia; Chasapi, Vasiliki; Sfaelos, Konstantinos; Cheliotis, George; Ioannides, Dimitrios
Abstract: Fixed combination calcipotriol/betamethasone (Cal/BD) aerosol foam has been shown to be effective in psoriasis treatment in clinical trials, but real‐world evidence is currently sparse. The real‐world CELSUS study in Greece found that Cal/BD aerosol foam treatment was effective and associated with satisfaction in psoriasis patients. Patients from the CELSUS study (N = 400) were stratified by baseline disease severity according to physician's global assessment (PGA) score (mild vs. moderate vs. severe) and by previous psoriasis treatment (naïve vs. treatment‐experienced). Proportions of patients achieving treatment success (clear/almost clear [PGA 0/1]) after 4 weeks' treatment with Cal/BD aerosol foam were reported for each subgroup. Psoriasis area and severity index (PASI) and patient‐reported itch, itch‐related sleep loss, scaling, dry skin, and erythema numerical rating scores were reported by subgroup. At baseline, 216 (54%) patients were systemic‐or‐topical psoriasis treatment‐naïve and 184 (46%) were treatment experienced. By disease severity, there were 135 versus 89 patients with mild, 69 versus 83 with moderate and 12 versus 12 with severe disease in the treatment‐naïve versus treatment‐experienced groups, respectively. In the treatment‐naïve group, treatment success was achieved by 72.6%, 56.5%, and 66.7% of patients with mild, moderate, and severe disease, respectively, while the proportions in the treatment‐experienced group were 60.7%, 42.2%, and 25%, respectively. Reduction from baseline in psoriasis symptoms was observed in all patient groups. The greatest reductions were observed in treatment‐naïve patients with severe disease. Clinically relevant benefits were observed with Cal/BD aerosol foam in psoriasis patients, regardless of prior treatment‐experience and disease severity at baseline.